2022
DOI: 10.3390/children9081209
|View full text |Cite
|
Sign up to set email alerts
|

Association between Molecular Mechanisms and Tooth Eruption in Children with Obesity

Abstract: Different works have reported earlier permanent teething in obese/overweight children compared to control ones. In contrast, others have reported a delayed permanent teething in undernutrition/underweight children compared to control one. It has been reported that becoming overweight or suffering from obesity can increase gingival pro-inflammatory drive and can affect orthodontic treatment (among other complications). In this sense, little is known about the molecular mechanisms affecting dental eruption timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Additionally, the researchers suggested that, in obese subjects, the probability of encountering premature incisors and permanent inferior first molars, is doubled. A significant correlation between body-weight at birth and primary dental eruption was also reported [18].…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, the researchers suggested that, in obese subjects, the probability of encountering premature incisors and permanent inferior first molars, is doubled. A significant correlation between body-weight at birth and primary dental eruption was also reported [18].…”
Section: Discussionmentioning
confidence: 78%
“…The impact of diet, characterized by nutrient-poor but energy-dense choices, and genetic and epigenetic factors further influences tooth development and eruption timing (Javaneh Vejdani et al, 2015 , Chava et al, 2018 ). Chronic low-grade inflammation associated with obesity may also affect signaling pathways regulating tooth eruption, contributing to early permanent tooth emergence ( Traver et al,2022 ). Understanding these interplays has broader implications for pediatric health, as early tooth eruption in obese children may increase susceptibility to decay and misalignment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity leads to metabolic changes, such as increased insulin secretion and growth factor, which can also play a role in the early tooth eruption ( 23 ). A recently published review brought some light on the orchestra of genes and molecules that possible may help to elucidate the molecular mechanisms linking obesity and tooth eruption ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the cited systematic review, other studies were published with conflicting results. While some authors found that increased body weight was associated with early tooth eruption and advanced dental age ( 11 - 14 ), others revealed contradictory evidence, such as lack of association ( 15 ) or an inverted relationship ( 16 ). Paz-Cortez, 2022 when evaluating a sample of patients between 4-14 years old, showed that body mass index (BMI) did not influence tooth eruption ( 15 ).…”
Section: Introductionmentioning
confidence: 99%